La question du retour d’expérience des stagiaires au sein des pratiques professionnelles de formateurs en insertion - Ioana Deicu (Recherches en Éducation)
This article describes the results of a study made between 2009 and 2010 in Haute-Normandie area, regarding the professional practices of a sample of trainers responsible for a training-insertion action. The reason of this research is to understand how important the internship is, especially the internship that is acquired within a company for training practices. After we’ll explain the problem and the methodology we utilized, we’ll show that even if the trainers offer to the apprentices a collective reflection time and space, regarding to their experience within the company, this analysis is in essence based on the requirements.